Prevalence and factors influencing physical activity among secondary school adolescents: A cross-sectional study - Nepal, Samata; Marhatta, Anu; Shrestha, Sajja; Karki, Deelip Kumar (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Physical inactivity is a major health concern among adolescents and is an independent, modifiable risk factor for several non-communicable diseases. Despite the World Health Organization recommended physical activity levels, many adolescents do not meet these guidelines. This study was conducted among secondary school students in Palpa district of Nepal to assess their physical activity levels and associated factors. Methods: A modified version of the Physical Activity Questionnaire Adolescents was used to collect data from 506 grade eight and nine students from six schools in Palpa district. Results: The results revealed that only 25.31% of students engaged in physical activity quite often or always, and only 23.10% met the daily WHO recommendation of at least 60 minutes of physical activity per day. Additionally, females were less likely to achieve the recommended physical activity level compared with males. Conclusions: The low levels of physical activity among secondary school students in Palpa district of Nepal highlight the need for interventions to promote physical activity. This study identified several factors associated with low physical activity levels, including limited break time at school, lack of parks or playgrounds near homes, and gender differences.